Interfirm Mobility, Wages, and the Returns to Seniority and Experience in the U.S. - Moshe Buchinsky; Denis Fougère; Francis Kramarz; Rusty Tchernis (Institute for the Study of Labor (IZA), 2005)
Much of the research in labor economics during the 1980s and the early 1990s was devoted to the analysis of changes in the wage structure across many of the world?s economies. Only recently, has research turned to the analysis of mobility in its various guises. From the life cycle perspective, decreased wage mobility and increased job instability, makes the phenomenon of increasing wage inequality more severe than it appears to be at first sight. In general, workers? wages may change through two channels: (a) return to their firm-specific human capital (seniority); or (b) inter-firm wage mobility. Our theoretical model gives rise to three equations: (1) a participation equation; (2) a wage equation; and (3) an interfirm mobility equation. In this model the wage equation is estimated simultaneously with the two decision equations. We use the Panel Study of Income Dynamics (PSID) to estimate the model for three education groups. Our main finding is that returns to seniority are quite high for all education groups. On the other hand, the returns to experience appear to be similar to those previously found in the literature.
Keywords: C11; J63; J31; C15; 330; wage mobility; interfirm mobility; returns to seniority; panel data; Markov Chain Monte Carlo methods